2015
DOI: 10.1021/acsami.5b04846
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of Carbon Nanotube Forests Consisting of Tubes with Narrow Inner Spacing Using Co/Al/Mo Catalyst on Conductive Supports

Abstract: We grow dense carbon nanotube forests at 450 °C on Cu support using Co/Al/Mo multilayer catalyst. As a partial barrier layer for the diffusion of Co into Mo, we apply very thin Al layer with the nominal thickness of 0.50 nm between Co and Mo. This Al layer plays an important role in the growth of dense CNT forests, partially preventing the Co-Mo interaction. The forests have an average height of ∼300 nm and a mass density of 1.2 g cm(-3) with tubes exhibiting extremely narrow inner spacing. An ohmic behavior i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 61 publications
2
27
1
Order By: Relevance
“…2d). 53,56 The I G /I D of CNTs grown at low process temperature (470°C) is comparable with that of pyrolyzed carbon at ∼1000°C, 46,48,64 indicating a similar degree of graphitization of the catalysed growth of CNTs by CVD. The side-view TEM image of the bottom part of the CNT forests shows Co particles, which mainly exist on the substrate surface with some being detached and incorporated into the CNT forests as shown with arrows in Fig.…”
Section: Characterization Of Cnt Forestsmentioning
confidence: 69%
See 1 more Smart Citation
“…2d). 53,56 The I G /I D of CNTs grown at low process temperature (470°C) is comparable with that of pyrolyzed carbon at ∼1000°C, 46,48,64 indicating a similar degree of graphitization of the catalysed growth of CNTs by CVD. The side-view TEM image of the bottom part of the CNT forests shows Co particles, which mainly exist on the substrate surface with some being detached and incorporated into the CNT forests as shown with arrows in Fig.…”
Section: Characterization Of Cnt Forestsmentioning
confidence: 69%
“…[50][51][52] In addition, by engineering the catalyst design, we showed that direct growth of dense CNT forests on conductive supports at 450°C in 3 min is possible. [53][54][55][56] They are suitable as electrode materials in IDEs as the CNTs have a highly packed morphology and good electrical contact with supports, which is different from the conventional CNT forests grown on insulators (e.g. SiO 2 , Al 2 O 3 , etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Elemental metals that are d-orbital vacancies-rich, such as Al, Mo, and Ti [ 27 , 29 , 32 , 36 ], were popular choices of diffusion barrier by adding an atomic-layer thin film in between the catalyst and the substrate. Sugime et al [ 27 ] simply added an Al film with a thickness of 5 Å in between the catalyst film and the substrate and found out that the diffusion of Co catalyst was prevented. Herein, catalyst nanoparticles with an areal density of 6–8 × 10 11 cm −2 were found to be effectively generated by thermal annealing.…”
Section: Synthesis Of High-density Cnt Arraymentioning
confidence: 99%
“…Recent works reported and revealed that CNT array can be reliably synthesized with high-density on metallic and insulating substrates, using the metal catalyst of nickel or cobalt [ 21 , 22 , 23 , 24 ]. Other works also explored approaches to reduce the CNT growth temperature while maintaining a high array density [ 25 , 26 , 27 , 28 , 29 ]. It turns out that the catalyst design has played a vital role in CNT synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, they have been widely employed as catalysts for the low temperature growth of carbon nanotubes. [20][21][22][23][24][25][26][27] However, attempts to grow polycrystalline thin-films of these metals have generally resulted in the formation of inhomogeneous multi-layer graphene. [28][29][30][31][32][33] This has often been attributed to the high carbon solubility of these metals, based on the assumption that carbon dissolved in the catalyst precipitates as multilayer graphene on cooling.…”
Section: Introductionmentioning
confidence: 99%